DEVELOPMENT OF LEARNING NEEDS BASIC DANCE STUDENT ON RAIL SANDRATASIK MAKASSAR STATE UNIVERSITY - Padalia, A. (Journal of Humanity, 2015)
Learning as a process of education that consists of different components that are interconnected to each other which includes the objectives, content, methods, and evaluation. Based on the phrase then it needs the skills of a teacher or educator to select and determine what learning devices to be used in the educational process.The selected learning device should be interactive, fun, challenging, inspiring, and motivating learners to participate actively.An interactive learning process expected teachers (candidates) can have the ability to membelajarkan learners so that learning can be done effectively and efficiently. Furthermore, he teaches the art of dance in College educational level, especially in Sendratasik education courses, aimed at mastering the skills and knowledge of dance as a provision for students when they teach at school or in the Studio. On Sendratasik education courses at this level do not use common names such as at primary and secondary level, but with more specific names based on the type of courses that exist within the structure of the curriculum education courses Sendratasik.